2017
DOI: 10.1159/000450830
|View full text |Cite
|
Sign up to set email alerts
|

Reviving Research on Medication Attitudes for Improving Pharmacotherapy: Focusing on Adherence

Abstract: There is little current interest in research into patients' attitudes toward medications. In the 1960s, psychiatric researchers including Uhlenhuth, Rickels and Covi focused on this area, but this research topic needs to be revived in the 21st century. The Health Belief Model may hold potential for doing this. This model was initially developed by 2 health psychologists, Rosenstock and Becker, to explain why patients did not follow medical interventions. The application of this model to study medication adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
(52 reference statements)
1
31
0
Order By: Relevance
“…About a quarter of patients (26.5%) were identified with DCPR criteria for illness behavior, which provides an explanatory model for clinical phenomena that do not find room in customary taxonomy [19-21]. The DCPR spectrum of illness behavior encompasses a number of syndromes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…About a quarter of patients (26.5%) were identified with DCPR criteria for illness behavior, which provides an explanatory model for clinical phenomena that do not find room in customary taxonomy [19-21]. The DCPR spectrum of illness behavior encompasses a number of syndromes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such an occurrence reflects the fact that, in clinical trials where differentiation according to cogent subgroups is made, a treatment which is helpful on average may be ineffective in some patients (no difference with placebo) and even harmful in someone else (worse than placebo) [53,54]. For instance, in psychiatric practice one can observe that certain types of patients seem to antagonize drug effects, whether this is due to psychological reactance (a motivational force that leads individuals to fear loss of control), the balance between internal and external health control beliefs, and illness behavior [55]. Such paradoxical clinical phenomena can be easily found in the setting of personality disturbances [56].…”
Section: Additive Versus Interactive Modelsmentioning
confidence: 99%
“…Treatment adherence [1] may be an important topic in clinical pharmacopsychology [2] (see online suppl. Introduction; see www.karger.com/doi/10.1159/000495940 for all online suppl.…”
mentioning
confidence: 99%
“…Pharmacophobia is one of the major variables associated with poor adherence [4] when measured by self-report in our Spanish studies, within the context of the Health Belief Model [1]. In a multivariate analysis of 940 psychiatric outpatients from Spain [5], we found that pharmacophobia was associated with poor adherence; the adjusted odds ratio (OR) was 2.54 (95% confidence intervals 1.84–3.50) after adjusting for the other 3 psychological dimensions known to influence poor adherence.…”
mentioning
confidence: 99%